The Phenomenology of Dementia : Time, Emotion, and Relationality in Life and Lifewriting - Barry , Elizabeth (Age, Culture, Humanities: An Interdisciplinary Journal, 2024)
This article will explore the subjective experience of time for people living with dementia, exploring the implications of the loss of the ability to expect, as well as to remember, and how this conditions lived experience. It will also look to intersubjective time as a condition of relationality and a structuring condition for reciprocal and empathic care. It uses an approach informed by neurobiology and phenomenology to analyze these forms of temporal experience, looking notably at features such as expectation and surprise, and their non-normative presentation in those living with dementia, following the methods of psychiatrist Eugene Minkowski, neurobiologist Francisco Varela, and philosopher Natalie Depraz. Finally, it will look to memoirs by those with dementia, as well those who live close to them, to add texture and emotional resonance to the scientific and philosophical accounts of time in dementia.